2021
DOI: 10.3390/antibiotics10020125
|View full text |Cite
|
Sign up to set email alerts
|

Bee Bread Exhibits Higher Antimicrobial Potential Compared to Bee Pollen

Abstract: This study aimed at investigation of the antimicrobial potential of ethanolic extracts of bee bread (BB) and bee pollen (BP) and suspensions of these products in MHB (Mueller Hinton Broth). We covered 30 samples of BP and 19 samples of BB harvested in Polish apiaries. Slightly lower activity was observed against Gram-negative bacteria compared to Gram-positive staphylococci. BB extracts exhibited higher inhibitory potential with minimum inhibitory concentration (MIC) values in the range from 2.5 to 10% (v/v) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
2
19
0
Order By: Relevance
“…The variability of biological properties could be attributed to differences in the botanical and geographical origin of the samples as well as to differences regarding the extraction methods used. Another possible explanation could be that most published studies on BB antimicrobial activity test but few samples (1–5) [ 1 ] with the notable exception of the very recent study by Pelka et al [ 49 ] on Polish BB. In order to correlate biological properties with botanical origin, a sufficient number of samples is required to represent both botanical diversity and geographical distribution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variability of biological properties could be attributed to differences in the botanical and geographical origin of the samples as well as to differences regarding the extraction methods used. Another possible explanation could be that most published studies on BB antimicrobial activity test but few samples (1–5) [ 1 ] with the notable exception of the very recent study by Pelka et al [ 49 ] on Polish BB. In order to correlate biological properties with botanical origin, a sufficient number of samples is required to represent both botanical diversity and geographical distribution.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial activity of bee bread was generally attributed to diverse phytochemicals, mainly polyphenols, fatty acids, phytosterols, and presumably microbial metabolites [ 1 ]. Pelka et al [ 49 ] reported no correlation between the phenolic content and antimicrobial activity of Polish BB. In accordance, this study does not report a statistically significant correlation between antibacterial and antioxidant activity or the total content of phytochemicals such as polyphenols or flavonoids ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted by Didaras et al [ 84 ], it was reported that the aqueous extract of Greek bee bread was effective against Gram-positive bacteria (MIC values ranging between 3.9 mg/mL and 48 mg/mL) and against Gram-negative bacteria (MIC values ranging between 7.8 mg/mL and 90.4 mg/mL). It has also been shown that bee bread ethanolic extracts (70%, 95%, 80%, and 50%) have strong antibiotic activity against Gram-positive bacteria ( Bacillus cereus , Clostridium perfringens, Staphylococcus aureus, Bacillus Subtilis, methicillin-susceptible Staphylococcus aureus, Staphylococcus epidermidis, and Listeria monocytogene ), Gram-negative bacteria ( Haemophilus influenza, Klebsiella pneumonia, Salmonella enteric, Escherichia coli, Shigella, Salmonella typhi , and Pseudomonas aeruginosa )and fungi ( Candida albicans, Aspergillus niger , Candida glabrata, Candida tropicalis , Aspergillus clavatus, Aspergillus flavus, Aspergillus versicolor, Penicillium expansum, Penicillium chrysogenum, and Penicillium griseofulvum ) [ 52 , 85 , 86 , 87 , 88 ].…”
Section: The Bioactive Effect Of Bee Bread: In Vitro Investigationsmentioning
confidence: 99%
“…Bee bread also has several health benefits including antioxidant [ 4 , 5 ], anti-inflammatory [ 6 ], anti-apoptotic [ 7 ], antimicrobial [ 3 , 8 ], anticancer [ 9 ], and immunological effects [ 10 , 11 ] on various tissues. Its effects on the male reproductive system cannot be over emphasised; our previous study has revealed that concurrent administration of a high-fat diet and 0.5 g/kg bee bread for twelve weeks showed protective effects against testicular oxidative stress, inflammation, and apoptosis in rats [ 12 ].…”
Section: Introductionmentioning
confidence: 99%